Comportamento de nidificação de melipona scutellaris na microrregião do brejo paraibano - Fernandes, Teotônio Lucas Sabino (2023)
The indian neem (Azadirachta indica) is a florestal species known for its insecticide properties, with azadirachtine being its main active compound and the basis for the production of natural bioinsecticides for the control of insects and plagues. However, this compound has been causing lethal injuries to pollinating insects, especially to bees. This study aimed to investigate the effects of the neem on the nesting behaviors of the stingless bee Melipona scutellaris. The study was conducted in two steps and in two areas composed of neem specimens, utilizing 10 standard hives with uruçu bees allocated within these trees. The assessment of the influence of the floral and leaf resources of the neem over the behavior of the bees was realized through the weighing of the hives, every fifteen days, to observe if the colonies would gain or lose weight. A comercial digital balance was used for the weighing, with a total of 6 weighings, totalizing 75 days of experiment. The information was registered and analyzed by means of polynomial regression, along with the box plot. The results attained for the first part of the study demonstrated weight gain and loss rates for the bee colonies, with loss rates being superior when compared to gain rates. After 30,45,60 and 75 days of observation, it was possible to notice a continuous weight loss in almost all hives, with a loss of 2.860 kg for hive 10 (6.540 kg – 3.680 kg), the biggest among all of them. The azadiractine active compound present in the leaves of the neem demonstrated toxicity over the colonies of the uruçu bees, resulting on a weigth and vigor loss for the swarms. On the second step of the study, it was not possible to obbtain sufficient data, due to the falling of the leaves and the consequent decrease of the quantity of flowers until the end of its floral cycle. However, it was managed to collect the data of hives 4 and 10, with the initial weights of 6.740 kg and 6.650 being registered, respectively, and after 15 days a weight loss was observed for hive 4 (6.630 kg) and hive 10 (6.420 kg). The pollen and nectar of the flowers of the A. Indica tree show a toxic action towards the bees brood which raised the mortality level of larvae in the colonies. Complementary research are necessary, especially with the obervation of the annual phenology, including flowering, with the offer of nectar and pollen, as a way to assess the impact over food supply for the uruçu bees. It is concluded that the collected data are indicative that, probably, the Indian neem favors a decrease of the uruçu colonies, established right under their tree tops, preventing the expressive gain (birth) of new workers. This study demonstrates the necessity not to plant the Indian neem on the colonies surroundings and the meliponaries of the species of uruçu bees.